2014
DOI: 10.3856/vol42-issue4-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

A review and analysis of Easter Islands traditional and artisan fisheries

Abstract: ABSTRACT. Based on a review of published and unpublished reports we analyzed Rapa Nui´s (Easter Island) traditional and artisan fisheries. We include information from 2000-2009 on landings, species, fishing grounds, fleet and number of fisherfolks according to the Servicio Nacional de Pesca (SERNAPESCA) and personal communication with SERNAPESCA officials. Presently, 29 species of fishes and two invertebrates are fished (along with a group of species reported as "non-identified"), primarily from the 10 main fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The reconstructed fishing history suggests that domestic fisheries catches have increased substantially since the late 1970s, mostly explained by the increase in offshore catches, specifically of T. albacares, which in turn may be related to the five-time growth in tourist arrivals on the island in the last 40 years. The estimated legal catches (Zylich et al, 2014) match the annual landing reported by Castilla et al (2014), ranging between 109 and 171 ton yr -1 during 2000-2009. Using different approaches Castilla et al (2014) and Zylich et al (2014) also conclude that a) yellowfin tuna is the main exploited species, and b) in spite temporal fluctuation, total catch has remained stable during the last decade.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…The reconstructed fishing history suggests that domestic fisheries catches have increased substantially since the late 1970s, mostly explained by the increase in offshore catches, specifically of T. albacares, which in turn may be related to the five-time growth in tourist arrivals on the island in the last 40 years. The estimated legal catches (Zylich et al, 2014) match the annual landing reported by Castilla et al (2014), ranging between 109 and 171 ton yr -1 during 2000-2009. Using different approaches Castilla et al (2014) and Zylich et al (2014) also conclude that a) yellowfin tuna is the main exploited species, and b) in spite temporal fluctuation, total catch has remained stable during the last decade.…”
supporting
confidence: 52%
“…The estimated legal catches (Zylich et al, 2014) match the annual landing reported by Castilla et al (2014), ranging between 109 and 171 ton yr -1 during 2000-2009. Using different approaches Castilla et al (2014) and Zylich et al (2014) also conclude that a) yellowfin tuna is the main exploited species, and b) in spite temporal fluctuation, total catch has remained stable during the last decade. However, fishery data collection is poor and there appears to be a lack of scientific rigor in the information collected, affecting the estimates of total catch.…”
supporting
confidence: 52%
See 3 more Smart Citations